Comparing Environmental Attitudes and Behaviors between an Indigenous and a Non-indigenous Sample from New Zealand and the United States of America - Snider, Anthony; Luo, Shanhong; Schell, Theresa; Hill, Jeffery (Environmental Management and Sustainable Development, 2021)
While there has been a substantial amount of literature published on environmental beliefs and behaviors, cross-cultural research in this area, particularly comparisons between indigenous vs. non-indigenous people, remains limited. The current study conducted a comparison of the environmental beliefs and behaviors, as well as political attitudes, between an indigenous and a non-indigenous sample of New Zealand and the US (total n=322). Respondents included students at the University of Waikato in New Zealand (Māori and European New Zealanders) and the University of North Carolina Pembroke in the US (Lumbees and non-indigenous Americans). The participants provided responses regarding their ecological worldview, belief in global climate change, and participation in environmentally responsible behaviors as well as their political attitudes, including system justification and political liberalism. Results showed that the New Zealand sample was more politically liberal and demonstrated more environmentally friendly beliefs and behaviors than the US sample. The indigenous group did not differ in their environmental beliefs or behaviors from their non-indigenous counterpart, but did endorse less system justification. Mediation analyses indicated that ecological worldview and belief in global climate change together fully mediated the link between political liberalism and environmentally responsible behavior. Implications of these findings for environmental behavior research and education are discussed.